2017
DOI: 10.1021/acs.jpcc.7b05416
|View full text |Cite
|
Sign up to set email alerts
|

Post-Mortem Analysis of Calendar-Aged 16 Ah NMC/Graphite Pouch Cells for EV Application

Abstract: Application of Li-ion batteries for transportation not only requires long cycling life but also the preservation of the electrochemical performance during the resting period. For certain car usage this resting time could be predominant compared with the cycling activity and is referred to as calendar aging. To understand the aging mechanisms during calendar aging, an extensive post-mortem study was conducted on commercial 16 Ah NMC/graphite pouch cells stored at 5, 25, 45, and 60 °C. The post-mortem analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 37 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…This indicateda ni nhomogeneous phase distribution over the electrode depth because the ratio between LiC 6 and LiC 12 was stronger.F rom simulations, more of the LiC 6 wase xpected to be located at the anode surface( near the separator). [45] This was in accordance with measurements [20,33,42,46] and simulations [17] that have shown that Li deposition (favored by high lithiationd egrees) [18,47] is also mostly located on the anode surface.…”
Section: Effects Of Temperaturea Nd Aging On the Intercalationmechanisupporting
confidence: 89%
See 1 more Smart Citation
“…This indicateda ni nhomogeneous phase distribution over the electrode depth because the ratio between LiC 6 and LiC 12 was stronger.F rom simulations, more of the LiC 6 wase xpected to be located at the anode surface( near the separator). [45] This was in accordance with measurements [20,33,42,46] and simulations [17] that have shown that Li deposition (favored by high lithiationd egrees) [18,47] is also mostly located on the anode surface.…”
Section: Effects Of Temperaturea Nd Aging On the Intercalationmechanisupporting
confidence: 89%
“…The loss of cyclable Lih as also been observed for other cells withoutS i compound in the anode. [39][40][41][42][43][44] Therefore, ap art of the capacity loss in the cells was likely to originate from the growth of a solid electrolyte interphase (SEI) layer on the graphite particles in addition to the aging effect of the Si compound;h owever,a large part of the film growth and the low coulombic efficiency can most likely be attributed to the formation of Li silicates.…”
Section: Relaxationmechanism After Charging In Fresh Cellsmentioning
confidence: 99%
“…In previous calendar aging‐related literature, as‐assembled cells were stored in various conditions (e.g., SOC, temperature, charging scenarios) over periods of >1 year to obtain detectable changes in the electrode materials and cell structures . It is very likely that limited electrolyte volumes and tightly assembled cell components are subject to slow progress.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared to the pristine electrode, the c ‐axis lattice parameters of both compositions are increased after aging, while the a ‐axis lattice parameters are slightly decreased. It seems that the decrease of Li content in the aged electrode materials increased the average oxidation state of the transition metal ions and the repulsive forces between slabs, yielding contracted a ‐axis and expanded c ‐axis lattice parameters . In addition, cross‐sectional SEM images of the electrodes before and after aging are observed to compare the mechanical stress incurred by the accelerated calendar aging (in Figure c–e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation